Cálculo de tiempos y costos medios para el pintado de vehículos en acabado tricapa (2018)
The realization of the project that has as title Calculation of times and average costs for painting in three-layer finish, was developed in conjunction with the area of research in painting of CESVI Colombia SA, collecting information on painting processes and making a sampling of the brands most sold in Colombia according to ANDEMOS (version 2.016), for the determination of the impact of said finishing in the automotive fleet and the figures of costing and productivity in time. Then a sampling of the most rotating three-layer colors was made; purchase orders were made for the process of painting, at the same time deducting the standard of process for painting and finalizing the process was reviewed with quality management to obtain the scale. All the information obtained will be attached in its entirety in a database.